USE OF EXTENDED-RELEASE PRAMIPEXOLE IN EARLY-STAGE PARKINSON’S DISEASE: DESCRIPTION OF A CLINICAL CASE - N. V. Fedorova; Ye. N. Gubanova (Klinicist, 2014)
The paper considers a clinical case of early-stage mixed Parkinson’s disease (PD) with significant affective disorders and restless legs syndrome. Once-daily extended-release pramipexole 3 mg significantly improved a patient’s status and led to regression of movement and affective disorders. The paper gives data on the efficacy of dopamine receptor agonists in treating PD and the benefits of their extended-release formulations.